PTPN22 gene functional polymorphism (rs2476601) in older adults with frailty syndrome - Rabaneda-Bueno, Rubén; Torres-Carrillo, Norma; Ávila-Funes, José Alberto; Gutiérrez-Robledo, Luis Miguel; Pérez-Suárez, Thalía Gabriela; Acosta, José Luis; Torres-Castro, Sara; Fletes-Rayas, Ana Lilia; Gutierrez-Hurtado, Itzae; Sandoval-Pinto, Elena; Cremades, Rosa; Torres-Carrillo, Nora Magdalena (Molecular biology reports, 2021)
The frailty syndrome is a common clinical marker of vulnerability in older adults conducive to an overall decline in inflammatory stress responsiveness; yet little is known about the genetic risk factors for frailty in elderly. Our aim was to investigate the association between the rs2476601 polymorphism in PTPN22 gene and susceptibility to frailty in Mexican older adults. Data included 630 subjects 70 and older from The Coyoacán cohort, classified as frail, pre-frail, and non-frail following Fried's criteria. Sociodemographic and clinical characteristics were compared between groups at baseline and after a multivariate analysis. The rs2476601 polymorphism was genotyped by TaqMan genotyping assay using real-time PCR and genotype frequencies were determined for each frailty phenotype in all participants and subsets by age range. Genetic association was examined using stratified and interaction analyses adjusting for age, sex and variables selected in the multivariate analysis. Disability for day-life activities, depression and cognitive impairment were associated with the risk of pre-frailty and frailty at baseline and after adjustment. Carrying the T allele increased significantly the risk of frailty in patients 76 and older (OR 5.64, 95% CI 4.112-7.165) and decreased the risk of pre-frailty under no clinical signs of depression (OR 0.53; 95% CI 0.17-1.71). The PTPN22 polymorphism, rs2476601, could be a genetic risk factor for frailty as subject to quality of life. This is the first study analyzing such relationship in Mexican older adults. Confirming these findings requires additional association studies on wider age ranges in populations of older adults with frailty syndrome.
Keywords: alely; Polymorphism, Single Nucleotide; křehký senior; Humans; PTPN22 gene polymorphism; křehkost; genetické asociační studie; Quality of Life; kohortové studie; Older adults; jednonukleotidový polymorfismus; Female; Aged; Phenotype; Alleles; senioři; lidé; Genotype; Mexico; kvalita života; Cohort Studies; Mexiko; ženské pohlaví; Frailty; Genetic Association Studies; Male; fenotyp; Genetic Predisposition to Disease; genetická predispozice k nemoci; SNP rs2476601; Aged, 80 and over; Frail Elderly; Protein Tyrosine Phosphatase, Non-Receptor Type 22; senioři nad 80 let; genotyp; Frailty syndrome; mužské pohlaví; tyrosinfosfatasa nereceptorového typu 22; Lymphoid tyrosine phosphatase locus (LYP/PTPN22); Multivariate analysis